2007
DOI: 10.1590/s1415-790x2007000300006
|View full text |Cite
|
Sign up to set email alerts
|

Ganho ponderal e desfechos gestacionais em mulheres atendidas pelo Programa de Saúde da Família em Campina Grande, PB (Brasil)

Abstract: OBJETIVO: Descrever o ganho ponderal e sua associação com os desfechos gestacionais em gestantes do Programa de Saúde da Família no município de Campina Grande, PB. MÉTODOS: Trata-se de um estudo longitudinal prospectivo desenvolvido de março de 2005 a março de 2006. O peso gestacional foi avaliado a cada quatro semanas a partir da 16ª semana gestacional. O cálculo do índice de massa corporal seguiu os critérios de Atalah (1997), adotados pelo Ministério da Saúde, e o ganho ponderal foi avaliado segundo recome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
1
16

Year Published

2010
2010
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(29 citation statements)
references
References 23 publications
1
5
1
16
Order By: Relevance
“…The evaluation of the nutritional status showed that a high percentage of the women started the pregnancy overweight/obese, a result slightly higher to that found in other studies developed in the primary healthcare system (7)(8)(9) . A cohort study that followed more than 3000 women attending general prenatal services of the Brazilian National Health System (SUS) found that 29%…”
Section: Discussioncontrasting
confidence: 65%
See 3 more Smart Citations
“…The evaluation of the nutritional status showed that a high percentage of the women started the pregnancy overweight/obese, a result slightly higher to that found in other studies developed in the primary healthcare system (7)(8)(9) . A cohort study that followed more than 3000 women attending general prenatal services of the Brazilian National Health System (SUS) found that 29%…”
Section: Discussioncontrasting
confidence: 65%
“…Other studies also found high percentages of pregnant women with weight gain above the recommended: 29% in Rio de Janeiro (17) ; 36% in Sao Paulo (18) ; 39%, 44% and 56% in pregnant women who started the pregnancy underweight, with adequate weight and overweight/obese, respectively, in Recife (9) ; 44% in Campina Grande, PB (8) ; and 45% in Rio Grande do Sul (11) . In addition to being associated with pre-gestational overweight/ obesity, excessive weight gain has been associated with the social variables of the women, such as better education and stable marital status (with partner) (9) .…”
Section: Discussionmentioning
confidence: 89%
See 2 more Smart Citations
“…Em relação ao período gestacional, o maior risco para complicações são para as gestantes obesas, que estão suscetíveis a diabetes, hipertensão, parto cirúrgico, enquanto seus filhos são mais propensos a apresentarem macrossomia, riscos de malformação fetal e maior mortalidade perinatal [6][7][8][9][10][11][12][13][14][15][16][17] . No entanto o baixo peso materno também aumenta os riscos de desfechos desfavoráveis para a mãe e para o concepto, entre os quais pode ser citada a restrição de crescimento intrauterino e a prematuridade 6,7,18,19 .…”
Section: Introductionunclassified